2022
DOI: 10.1109/jstars.2021.3132360
|View full text |Cite
|
Sign up to set email alerts
|

GF-4 Satellite Fire Detection With an Improved Contextual Algorithm

Abstract: The GF-4 satellite has a moderate spatial resolution and is capable of high temporal frequency observation. Thus, it can play an important role in the acquisition of information regarding fires. In this study, the characteristics of brightness temperature difference between fire point area and non-fire point area are comprehensively analyzed. Employing the advantages of high-frequency continuous observation of these data, an improved algorithm for joint spatial attribute detection using multi-temporal data is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…With the development of satellite remote sensing, many research scholars began to notice the efficiency of remote sensing satellite images for residue fire points monitoring [14][15][16]. These studies found that remote sensing technology can provide dynamic macro monitoring of residue fire information.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of satellite remote sensing, many research scholars began to notice the efficiency of remote sensing satellite images for residue fire points monitoring [14][15][16]. These studies found that remote sensing technology can provide dynamic macro monitoring of residue fire information.…”
Section: Introductionmentioning
confidence: 99%